ความพึงพอใจในการปฏิบัติงานของเจ้าหน้าที่ศูนย์สงเคราะห์และฝึกอาชีพสตรีในประเทศไทย - วิภาวดี จันทยงค์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The objectives of this research were to : examine and compare the level of job satisfaction of officers of the welfare and vocational training centres for women in Thailand. The factors as referred here were sex, age, experience, level of education, position, and self-actualisation. Sampling group were 143 officers working in the welfare and vocational training centres for women in Thailand. Tool for this research was questionnaire. Analyzing data by calculating frequency, percentage, mean, standard deviation, t-test, One way analysis of variance (one-way ANOVA) and Lest Significant Differential (L.S.D) Test. The research finding were : 1. Level of job satisfaction of officers of the welfare and vocational training centres for women in Thailand was at the most satis factors. Separately into 6 areas: responsibility; work achievement; job description; job secure, relationship with colleagues and superiors; and working environment, level of job satisfaction was at most satisfied. Level of satisfaction was moderate in 6 areas: esteem needs; working and individual life, policy and management; work supervisor, advancement in work; and salary and compensation. 2. The comparison of levels of job satisfaction of officers of the welfare and vocational training centres for women in Thailand were not different among age, level of education and position. The comparison of levels of job satisfaction of officers of the welfare and vocational training centres for women in Thailand were different among sex, experience and self-actualisation satisfied.